Suicidal behavior in children and adolescents - Wagner, Barry M. (Current perspectives in psychology, 2009)
Introduction -- Nature and scope of the problem -- Theoretical and developmental considerations -- Social relationships -- Stress, coping, and emotion regulation -- Psychopathology -- Assessment and treatment -- Prevention